Bionanocomposites from spent hen proteins reinforced with polyhedral oligomeric silsesquioxane (POSS)/cellulose nanocrystals (CNCs). (August 2022) - Zubair, Muhammad; Wu, Jianping; Ullah, Aman
Abstract: The utilization of bio-renewable and environmentally sustainable materials has been growing tremendously. Spent hen is a major poultry industry by-product; in this study, we aimed to develop spent hen proteins (SHP) based films for food packaging applications. The spent hen proteins were modified with cellulose nanocrystal (CNCs) and glycidyl polyhedral oligomeric silsesquioxanes (POSS) individually and transformed into bionanocomposite films using compression molding. All protein derived bionanocomposite films were characterized by dynamic mechanical analysis (DMA), attenuated total reflectance-fourier transform infrared spectroscopy (ATR-FTIR), X-ray diffraction (XRD), differential scanning calorimetry (DSC), transmission electron microscopy (TEM) and thermal gravimetric analysis (TGA). The incorporation of CNCs and POSS as a reinforcing agents into the protein's polymer matrix showed a substantial increase in the mechanical strength, water barrier and thermal properties. The mechanical strength of neat protein films increased from 2.65 ± 0.50 to 6.47 ± 0.50 MPa and 8.48 ± 0.98 MPa with POSS (3%) and CNCs (5%), respectively. The strong interactions of nanoparticles with proteins were observed which improved the physical and thermal properties of the spent hen proteins derived films. Thus, POSS or CNCs modified spent hen protein films being renewable and environmentally benign, have great potential to be used as a food packaging material to replace petroleum based polymers. Graphical abstract: Image 1 Highlights: Spent hen proteins based films have the potential to substitute petroleum derived food packaging materials. The nanoreinforcements of spent hen proteins with CNCs and POSS improved the films tensile strength. The incorporation of CNCs (5%) and POSS (3%) improved mechanical strength up to 3.5 folds.